Comparative study of positioning and technical-tactical indicators between teams of different performance levels in the Qatar 2022 FIFA World Cup - Iván-Baragaño, I.; Casal, C. A.; Maneiro, R.; Losada, J. L. (Kinesiology, 2024)
The aim of the study was to identify the technical-tactical indicators and differentiate collective positioning between the qualified teams and teams non-qualified for the final phase of the FIFA World Cup Qatar 2022, considering effective playing time. The aim was also to understand the interaction of variables that significantly increased the likelihood of being qualified in the analysed championship. We conducted a comparative analysis that covered all matches played (N=64), evaluating 93 technical-tactical indicators, 24 collective positional indicators and six hybrid indicators. The absolute technical-tactical indicators were normalised based on the effective playing time of each team in each match. We used t-tests and binary logistic regression (R2 Nagelkerke = .738 - AUC = .955) to analyse differences and determine their statistical significance (p<.05). Our analysis revealed significant differences in 33 indicators, suggesting that certain technical-tactical aspects played a crucial role in teams` performance. Furthermore, through multivariate analysis, we were able to identify that offensive efficiency in set pieces, the height of the defensive line during the offensive phase, and the ability to reduce the available playing space for the opposing team during the defensive phase emerged as the main indicators that allowed us to classify the teams` performance. These findings enable coaches to use the identified key indicators as performance predictors to devise match strategies aimed at enhancing the effectiveness of their teams.